Optimization of Cash Waqf Linked Sukuk (CWLS) for supporting Indonesia’s economic recovery post-Covid-19 era - Sulaeman Sulaeman; Siti Zubaidah; Tika Nur’atikah (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – The purpose of this study is to analyze the optimization of the Cash Waqf Linked Sukuk (CWLS) issuance mechanism and its potential to support Indonesia's economic recovery after the Covid-19 pandemic.Methodology – This study uses a qualitative descriptive analysis approach by exploring the relevant literature. This study also uses the SWOT (Strength, Weakness, Opportunity, and Threat) to obtain information on internal and external factors that can support and inhibit the planned issuance of CWLS.Findings – This study found that the investment returns from cash waqf funds in the CWLS model can be utilized for social and economic development in Indonesia. In line with the objectives of Indonesia's economic recovery program, namely: aiming to protect, maintain, and improve the economic capacity of business actors, especially MSMEs, in running their business during and after the Covid-19 pandemic in Indonesia.Implications – The CWLS model is expected to make a positive contribution to the Indonesian government and policymakers as material for further study of Islamic financing instruments, which can optimize their role in supporting the financing of Indonesia's economic recovery programs during and after the Covid-19 pandemic.Originality – The novelty of this research is proposing an alternative source of financing for the government in supporting Indonesia’s economic recovery. Further, this research contributes to the existing literature on Islamic social finance, especially for waqf studies.